8x+6=2x-30

Simple and best practice solution for 8x+6=2x-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+6=2x-30 equation:


Simplifying
8x + 6 = 2x + -30

Reorder the terms:
6 + 8x = 2x + -30

Reorder the terms:
6 + 8x = -30 + 2x

Solving
6 + 8x = -30 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
6 + 8x + -2x = -30 + 2x + -2x

Combine like terms: 8x + -2x = 6x
6 + 6x = -30 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + 6x = -30 + 0
6 + 6x = -30

Add '-6' to each side of the equation.
6 + -6 + 6x = -30 + -6

Combine like terms: 6 + -6 = 0
0 + 6x = -30 + -6
6x = -30 + -6

Combine like terms: -30 + -6 = -36
6x = -36

Divide each side by '6'.
x = -6

Simplifying
x = -6

See similar equations:

| 6m+3=33 | | 9x-8=5x+5 | | 0.5*n(n-3)=54 | | -3x-17=-2 | | 8x-2+3x=13x+8 | | -11=x+16 | | 11w=3520 | | z-3=30 | | 10c=70 | | 5w+6=9w+3 | | q-6=6 | | 4=m-2 | | 12+g=16 | | t+15=19 | | sqrt(3x+2)=xsqrt(2) | | 12=((-3+1)(-3+1))(k) | | =x^4-6x^3+13*x^2-12*x+5 | | 0.5x(x-3)=54 | | x=2(6+2x)+8x | | 8x-20=2x-8 | | A=5*5*5(3.5) | | w+3/4=6 | | 3x+2=x^2-2 | | px^2-6x+p=0 | | 2x-36+x=90 | | 3x=2+5 | | 3j-9=6 | | 4x^2y-6xy^2=u | | 3x+x+2+4=18 | | x^2+x^2=c | | 9m-9=-45 | | x^2*X^2=c^2 |

Equations solver categories